2005
DOI: 10.1081/clt-58950
|View full text |Cite
|
Sign up to set email alerts
|

Key Concepts in Postmortem Drug Redistribution

Abstract: Postmortem redistribution (PMR) refers to the changes that occur in drug concentrations after death. It involves the redistribution of drugs into blood from solid organs such as the lungs, liver, and myocardium. Drug properties such as volume of distribution, lipophilicity, and pKa are important factors. Basic, highly lipophilic drugs with a volume of distribution greater than 3 l/kg are most likely to undergo PMR. Examples include the tricyclic antidepressants, digoxin, and the amphetamines. The anatomical lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 52 publications
3
70
0
5
Order By: Relevance
“…Also, our results were consistent with Schier et al, 2010 who reported the same finding [13]. It is well documented that most drugs and toxic agents undergo post-mortem redistribution, particularly drugs in cardiac blood is affected by post-mortem redistribution from surrounding tissue (e.g., lung, gastrointestinal tract, and myocardium) [23,24]. Moreover, drugs excreted in the liver may be redistributed via the hepatic veins to inferior vena cava, right cardiac chamber, and pulmonary vessels [19].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Also, our results were consistent with Schier et al, 2010 who reported the same finding [13]. It is well documented that most drugs and toxic agents undergo post-mortem redistribution, particularly drugs in cardiac blood is affected by post-mortem redistribution from surrounding tissue (e.g., lung, gastrointestinal tract, and myocardium) [23,24]. Moreover, drugs excreted in the liver may be redistributed via the hepatic veins to inferior vena cava, right cardiac chamber, and pulmonary vessels [19].…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, drugs excreted in the liver may be redistributed via the hepatic veins to inferior vena cava, right cardiac chamber, and pulmonary vessels [19]. The same principle apply to metals; Cd accumulates in very high concentrations in various body tissues (especially liver and kidney) during life [23,25,26]. However, inequitable distribution of red blood cells due to clotting or hypostasis cannot explain increased post-mortem whole blood Cd level [7].…”
Section: Discussionmentioning
confidence: 99%
“…Doubtlessly, knowledge of the mean ratio of drug concentration in cardiac tissue to that in blood (even measured postmortem) may be useful in predicting the myocardial concentration if the drug blood level is known [8]. The factors affecting the postmortem redistribution of drugs were reviewed by Yarema and Becker [9]. We will mention herein only those facts that appear to matter most in determining the myocardial postmortem drug concentration.…”
Section: Introductionmentioning
confidence: 99%
“…In Analytical Toxicology the limiting step is the "time", while in Forensic toxicology it is crucial to achieve incontestable laboratory data, and in this setting it is also crucial to define properly what Quality of Toxicological results [1][2][3][4].…”
Section: Aims: Clinical/analytical Toxicology Versus Forensic Toxicologymentioning
confidence: 99%